Teachers’ Perception on the Implementation of English as Medium Instruction for Young Learners - Lesmana, Bayu; Annisa Astrid; Eko Saputra (Jadila: Journal of Development and Innovation in Language and Literature Education, 2024)
The purpose of the study was to ascertain how educators felt about using English as a teaching language for younger students. The method employed in this investigation was qualitative. The teachers at Pesantren Syuhratul Islam Gelumbang who use English to teach subjects other than English were the ones who were chosen to participate in this study. Based on the consideration, two teachers were chosen to be the research participants. The participants in this study were chosen through the use of a deliberate sampling strategy. The researcher employed observation and interview techniques to get information from the participants regarding this study. The data regarding the challenges teachers face while implementing English as a medium of instruction for young learners was studied by the researcher using thematic analysis. The result of this study showed that there were several perceptions from the teachers on the use of English as a medium of instruction: 1) EMI develops student communication skill; 2) EMI makes student listening skill better; 3) Teachers feel difficult to ensure the students to achieve the learning objective; and 4) Teachers feel difficult in determining teaching method. The study’s conclusions suggested that English as a medium of education presented a number of challenges for teachers. They have therefore prepared effective teaching techniques that should be understood by the students and make for a more pleasurable learning environment in the classroom.